Editorial - "Information Pollution, Crimes, Harms, and Criminal Justice: Untangling the Nexus" - Miró Llinares, Fernando (European journal on criminal policy and research, 2025)
Although information pollution is not a new phenomenon, the expansion of social media and the new architecture of cyberspace have profoundly transformed both its scale and impact. From a criminological perspective, the creation and propagation of polluted information is now considered a distinguishing criminogenic and harming feature of our societies that, beyond enabling or facilitating diverse harms, can have a direct impact on a broad range of crimes both online and offline, and shape public opinion about crime and deviance. Through this Special Issue, we further stimulate criminological thinking in this direction, recognizing the unique insights that criminological imagination can offer in unpacking, understanding and countering information pollution.